Student Life in Medieval Times in France and Marius Mircu's Student Experience in Romania - Carmen Țâgșorean (University Babes-Bolyai, 2020)
The progress of a society is partially conditioned by education, a condition valid both in the past and in the present, the education systems having particularities specific to times and people. Marius Mircu, the Romanian journalist of Jewish origin, born at the beginning of the 20th century, in Bacău, grew up and was educated in the middle of one of the communities that paid special attention to the learning process. Our paper will explore some of his works concerning higher education institutions. The love for the study was passed on through his press articles and volumes dedicated to this topic. For the purpose of this paper we want to bring up to date Mircu's works concerning two moments in the history of European higher education, namely the Middle Ages in France (with a focus on Paris) and the University of Bucharest - Faculty of Law (mid-20th century).